A brief review laser joining of polymer-metal structures. - Farazila, Y. (Asean Engineering Journal)
Joining of dissimilar materials especially in the case of polymer and metal structure is significantly challenging due to the difference in chemical, mechanical and thermal properties of materials. Traditionally, metal and plastics are joined together either mechanically or by using adhesives. However, these techniques have limited use in joining small sized and intricately shaped parts. To address this limitation, constant effort on the development of reliable joining processes for polymer-metal structures are currently being explored. This article provides a brief review of joining polymer and metal using laser joining technique. A summary of relevant works carried out in recent years, the choices of lasers available, the most suitable laser technique, the mechanism of joining and significant findings by selected researchers are presented in this article.